Cytotoxicity and Genotoxicity of Cypermethrin in Hepatocarcinoma Cells: A Dose- and Time-Dependent Study - Abdullah A. AlKahtane PhD; Saud Alarifi PhD; Ahmed A. Al-Qahtani PhD; Daoud Ali PhD; Suliman Y. Alomar PhD; Mohammed S. Aleissia PhD; Saad Alkahtani PhD (Dose-Response, 2018)
Most of the agricultural workers are potentially exposed to pesticides through different routes. Inhalation exposures may result in numerous diseases that can adversely affect an individual’s health and capacity to perform at work. The aim of this study was to determine the cytotoxic potential of cypermethrin pesticide on cultured human hepatocarcinoma (HepG2) cells. The HepG2 cells were exposed to cypermethrin (0, 5, 15, 40 ng/mL) for 24 and 48 hours. We observed that cypermethrin caused cell death of HepG2 cells using 3-(4, 5-dimethylthiozolyl-2)-2,5-diphenyl tetrazolium bromide (MTT) and lactate dehydrogenase tests. Furthermore, cypermethrin reduced HepG2 cells viability in a time and dose dependent basis, that was probably mediated through the induction of reactive oxygen species (ROS) and apoptosis. An increase in ROS generation with a concomitant increase in expression of the proapoptotic protein Bcl-2 and cytochrome c and decrease in the antiapoptosis protein Bax suggested that a mitochondria-mediated pathway was involved in cypermethrin-induced apoptosis. These findings provide insights into the underlying mechanisms involved in cytotoxicity of cypermethrin in HepG2 cells.